PERAN PENDIDIKAN AGAMA ISLAM PADA MAJELIS TAKLIM AL-HIDAYAH DALAM MENINGKATKAN PEMAHAMAN BAHAYA GHIBAH BAGI IBU RUMAH TANGGA - Hani, Umi; Maksum, Ali (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2022)
This research is motivated by the existence of the Al-Hidayah taklim assembly in the midst of the Ciawi Hamlet community, which does not make the phenomenon of backbiting in society recede. Most of the people who do backbiting are housewives as well as members of the Al-Hidayah taklim assembly itself. This study was conducted to determine the extent to which housewives understand about backbiting, the role of the Al-Hidayah taklim assembly and the supporting and inhibiting factors of the Al-Hidayah taklim assembly in increasing the understanding of the dangers of backbiting for housewives in Astana Hamlet. This research method uses a qualitative type. The data collection techniques include interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study indicate that the understanding of housewives in terms of understanding backbiting has increased, but has not been maximized. This is indicated by the presence of the majority of housewives who have not been able to apply the understanding of the dangers of backbiting obtained in everyday life. As for the role of the Al-Hidayah taklim assembly in increasing understanding of the dangers of backbiting, this has been maximally pursued. The supporting factor for the Al-Hidayah taklim assembly in increasing the understanding of the dangers of backbiting for housewives is the knowledge of backbiting itself. While the personal self of each congregation is a supporting factor as well as an obstacle for the Al-Hidayah taklim assembly in increasing the understanding of the dangers of backbiting for housewives